2010
DOI: 10.1186/1757-2215-3-16
|View full text |Cite
|
Sign up to set email alerts
|

Serum and follicular anti-Mullerian hormone levels in women with polycystic ovary syndrome (PCOS) under metformin

Abstract: BackgroundNo data regarding metformin effects on follicular fluid anti-Müllerian hormone (AMH) levels were to date available in literature. The aim of the present study was to evaluate in patients with polycystic ovary syndrome (PCOS) whether metformin administration affects serum and follicular AMH levels, and whether this is related to ovarian response to the treatment.MethodsTwenty young patients with PCOS who had received metformin were enrolled. Ten patients were anovulatory (Met-anov group), whereas the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 30 publications
3
12
0
Order By: Relevance
“…It is also reported that metformin is more effective at insulin resistance but oral contraceptives were more beneficial at amelioration of menstrual irregularity and hyperandrogenemia (20). Also, its effect is proven on serum AMH levels in patients with PCOS (21,22). In our study, Serum AMH levels were significantly higher in patients with PCOS when compared to healthy women.…”
Section: Discussionsupporting
confidence: 58%
“…It is also reported that metformin is more effective at insulin resistance but oral contraceptives were more beneficial at amelioration of menstrual irregularity and hyperandrogenemia (20). Also, its effect is proven on serum AMH levels in patients with PCOS (21,22). In our study, Serum AMH levels were significantly higher in patients with PCOS when compared to healthy women.…”
Section: Discussionsupporting
confidence: 58%
“…Studies have attempted for years to show an advantage to metformin for ovulation induction and as an adjunct to more advanced fertility treatments. In ovulatory PCOS wo men metformin was associated with improved serum and follicular fluid AMH levels as well as insulin values; these changes were not seen in anovulatory PCOS women [71] . Despite the demonstration of negative effects of IR on reproductive outcome, the vast majority of evidence does not show improvement in live birth rates when metformin is used strictly for fertility [72] , although treatment does im prove ovulatory status [72,73] .…”
Section: Treatmentmentioning
confidence: 81%
“…Second, metformin also affects the ovarian environment by improving intraovarian hyperandrogenism and insulin resistance in experimental studies (17,34). Androgens stimulate the early stages of follicular growth by enhancing granulosa FSH receptor expression via an increase in the number of FSH-responsive follicles (35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 98%